2017
DOI: 10.1111/anu.12539
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plant-based diet and suboptimal environmental conditions on digestive function and diet-induced enteropathy in rainbow trout (Oncorhynchus mykiss )

Abstract: This experiment investigated intestinal enteropathy and digestive function of rainbow trout challenged with soybean meal-based diet (SBM) at optimal or suboptimal environments created by normal or reduced water flow, respectively. Oxygen level remained above 7 mg L -1 for optimal environment and between 4 and 5 mg L -1 for suboptimal environment. Triplicate groups of fish (mean body weight 74 g) were fedfishmeal-based diet (FM) or SBM at optimal environment in period 1 (28 days). In period 2 (42 days), fish we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Fish intestine health status was determined by endogenous and exogenous materials, in which the feedstuffs had been extensively researched [ 16 ]. It has earlier been established that the plant protein supplemented in the diet impairs the intestinal health status in several carnivorous fish species, accompanied with poor nutrient digestibility [ 17 26 ]. Our previous work also revealed that dietary soybean meal induced intestinal enteritis and reduced the digestive and absorptive functions in turbot [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fish intestine health status was determined by endogenous and exogenous materials, in which the feedstuffs had been extensively researched [ 16 ]. It has earlier been established that the plant protein supplemented in the diet impairs the intestinal health status in several carnivorous fish species, accompanied with poor nutrient digestibility [ 17 26 ]. Our previous work also revealed that dietary soybean meal induced intestinal enteritis and reduced the digestive and absorptive functions in turbot [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the carbohydrate fraction on histological tissues has not been enough studied. The negative effects of plant ingredients are mainly due to the presence of non-starch polysaccharides and antinutritional factors (Mosberian-Tanha et al 2017). The inclusion of soybean meal has shown to develop histological alterations in the intestine of Atlantic salmon and rainbow trout such as a shortening of mucosal folds, a loss of the normal supranuclear vacuolation of the absorptive cells in the intestinal epithelium, a widening of the central stroma within the mucosal folding, infiltration of inflammatory cells in the lamina propria or enteritis , Refstie et al 2000, Krogdahl et al 2003.…”
Section: Effect Of Feed On Rainbow Trout Histologymentioning
confidence: 99%
“…Wolf and Wolfe (2005) reported that these alterations could be macroscopically visible as changes in liver size. Under intensive rearing of Atlantic salmon, a decrease on the water-dissolved oxygen creates a stress on fish increasing the permeability of the intestinal walls (Olsen et al 2002, Mosberian-Tanha et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations